Beau's Lines and Onychomadesis: A Systematic Review of Characteristics and Aetiology - Bo Ri Kim; Da-Ae Yu; Soo Ran Lee; Sophie Soyeon Lim; Je-Ho Mun (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)